A Digital Twin of Hot Pumping Waxy Oil Through a Main Pipeline - Uzak Zhapbasbayev; Timur Bekibayev; Gaukhar Ramazanova; Zhibek Akasheva (Energies)
This article presents a digital twin of hot pumping waxy oil through a main pipeline. Digital copies of the original object data were identified through sensor measurements from SCADA and ECMAS, forming the basis of the SmartTranPro 1.7.1 Software. The mathematical model of the software describes the process of hot pumping waxy oil regarding heat exchange with the environment. The intelligent algorithms of the SmartTranPro 1.7.1 Software were used to determine the actual dependencies of the digital twins of the objects, hydraulic parameters, and heat transfer for the Kassymov–Bolshoi Chagan hot main pipeline, which has a length of 450 km. The results of the thermal–hydraulic calculations for the hot pumping of waxy oil are in good agreement with the actual sensor data from SCADA and ECASM. The optimization calculations of the heating temperature for waxy oil show an economic efficiency of 38.9% for the hot pumping method.